HUBUNGAN DUKUNGAN KELUARGA DAN PERAWAT DENGAN MOTIVASI PASIEN KANKER KOLOREKTAL DALAM MENJALANI KEMOTERAPI - AKHMAD MUKHLIS (LPPMK STIKES Widyagama Husada, 2022)
ABSTRACT Chemotherapy can cause physiological and psychological impacts that cause some patients to feel afraid to do chemotherapy, for this reason, family support and nurse support are needed so that colorectal cancer patients remain motivated to undergo chemotherapy. The purpose of this study was to determine the relationship between family support and nurse support on patient motivation to undergo chemotherapy in colorectal cancer patients at Dr. Saiful Anwar Hospital Malang. The design used is a correlation study to study the relationship between the independent variables of family support and nurse support, the dependent variable is the motivation of patients undergoing chemotherapy. Data collection is a cross sectional study using an instrument in the form of a questionnaire. By using the purposive sampling technique, a sample of 40 people was obtained. The research was conducted at Dr. Saiful Anwar Hospital, Malang. The results of the Rank Spearman correlation test show that there is a relationship between family support and motivation in colorectal cancer patients of 0.347 (p=0.028), the relationship is positive/unidirectional with moderate strength, the better the family support, the better the motivation of colorectal cancer patients undergoing chemotherapy. With family support helps cancer patients to increase their confidence that they are accepted by their families, thus providing motivation to do chemotherapy regularly in order to recover. The results of the Rank Spearman correlation test showed that there was a relationship between nurse support and motivation in colorectal cancer patients of 0.490 (p=0.000), the relationship was positive/unidirectional with moderate strength, the better the nurse support, the better the motivation of colorectal cancer patients undergoing chemotherapy. Because with the support of nurses, it will increase the patient's knowledge about chemotherapy and healing, thereby increasing the patient's motivation to undergo chemotherapy. Keywords: Colorectal cancer, chemotherapy, family support, nurse support, motivation